Liberdade e imoralismo em Nietzsche - Alice Parrela Medrado (2021)
This work elaborates the idea that, contrary to western tradition, Nietzsche does not conceive of freedom as a condition of non-impediment, but rather as a type of disposition in whose roots one would identify the instinct of freedom. Such instinct is understood as the support for a commitment with the value of freedom, on which basis one may sustain an opposition to morality’s regime. Along the text, we approach the different steps in the elaboration of a properly nietzschian concept of freedom and we follow the theme of freedom as a guide-line into the debate on some of the central issues of Nietzsche’s philosophy: criticism of the morality of free-will; revision of the terms traditionally used for describing action and ascribing responsibility; the program of cultural intervention in terms of penal abolitionism; the confrontation with the moral point of view and the theme of self-cultivation.